Genetic diversity and spatial genetic structure in populations of Orbignya phalerata Mart. under different exploitation intensities in the Brazilian savanna - Ibanes, B.; Sebbenn, A. M.; Azevedo, V. C. R.; Moreno, M. A.; Gandara, F. B.; Tambarussi, E. V. [UNESP]; Ferraz, E. M.; Damasceno-Silva, K. J.; Lima, P. S. C.; Carvalhaes, M. A. (De Gruyter Poland Sp Zoo, 2015)
Genetic studies in tropical tree species have found signs of decreased genetic diversity and increased levels of inbreeding and spatial genetic structure (SGS) in fragmented and exploited populations. The aim of this paper was to investigate genetic diversity, structure, and intrapopulation SGS using eight microsatellite loci for three Orbignya phalerata populations that have undergone different intensities of seed harvesting. From each population, we georeferenced and sampled 30 seedlings, 30 juveniles, and 30 adult trees. The total number of alleles over all loci (k), and observed (H-o) and expected heterozygosity (H-e) presented lower values for the population experiencing more intense fruit harvesting than less heavily exploited populations, suggesting that fruit harvesting may decrease genetic diversity. Null alleles were detected in practically all loci among seedlings, juveniles, and adults in all populations, indicating that the estimates of H-o, H-e, and fixation index (F) are biased. When corrected for null alleles (F-Null), the fixation index decreased for all samples, resulting in significantly higher than zero results for seedlings of all populations, but not for juveniles and adults of all populations. The comparison of F-Null values between cohorts in the most heavily exploited population (ESP) suggests that inbred individuals are eliminated between seedling and adult stages. Significant SGS was detected up to 60 m in all populations, which indicates short distance seed dispersal. Genetic differentiation (G'(ST)) between pairwise populations was related to spatial distance between populations, with the greatest difference between more distant populations.
Keywords: babassu; Orbignya phalerata; forest management; exploitation; genetic diversity